Let a = cost of an apple and p = cost of a peach
From the two statements we can create the following system of equations:
2a + 3p = 1.65
3a + 2p = 1.60
Since we want to know the cost of a peach, let's eliminate the "a" terms by creating opposites. The LCM for 2 and 3 is 6 so I will multiply the top equation by 3 and the bottom equation by -2. This will create opposites to cancel "a" terms.
3(2a + 3p = 1.65) → 6a + 9p = 4.95
-2(3a + 2p = 1.60) → -6a - 4p = -3.20
The result of adding → 5p = 1.75
The result of ÷ 5 → p = .35
This means one peach cost .35 or 35 cents